Firm heterogeneity, rules of origin and rules of cumulation - Pamela Bombarda; Elisa Gamberoni (Graduate Institute of International and Development Studies, 2008)
We analyse the impact of relaxing rules of origin (ROOs) in a simple setting with heterogeneous firms that buy intermediate inputs from domestic and foreign sources. In particular, we consider the impact of switching from bilateral to diagonal cumulation when using preferences (instead of paying the MFN tariff) involving the respect of rules of origin. We find that relaxing the restrictiveness of the ROOs leads the least productive exporters to stop exporting. The empirical part confirms these results. We use the most recent techniques developed by Helpman, Melitz and Rubinstein (2007) on highly disaggregated data (HS6 digit) to analyse the effects of the introduction of the Pan-European Cumulation System (PECS). We find that PECS reverses the negative impact of strict ROOs on intermediate trade which turns positive as a consequence of introducing diagonal rules of cumulation (ROCs).
Keywords: F12; F13; F14; F15; 330; Intermediate goods; Rules of origin; Rules of cumulation; Firm heterogeneity; Gravity; Vorprodukt; Herkunftsbezeichnung; Protektionismus; Handelspräferenzen; Unvollkommener Wettbewerb; Theorie; EU-Staaten